ANALISIS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DASAR: KOMPETENSI, BUDAYA DAN INOVASI DI UPT SPF SD NEGERI BTN IKIP II - Sitti Nur Annisa Muharyati; Suardi; Idawati (STKIP Subang, 2025)
This study aims to evaluate the leadership of school principals in the context of 21st-century education, focusing on the five competencies of school principals as outlined in the Ministry of Education and Culture Regulation No. 6 of 2018. This study also analyzes the implementation of transformational leadership and spirituality, as well as the strategies used by school principals in building a positive school culture. The methodology employed includes interviews, observations, questionnaires, and documentation with subjects consisting of the School Principal and Teachers at UPT SPF SD Negeri BTN IKIP II. The results of the study indicate that the school principal applies a democratic and transformational leadership style, which focuses on managing the school's vision and mission while motivating relevant parties to achieve shared goals.